Does CEO age affect the performance of banks in Indonesia? - Dalimunthe, Sholatia; Sabila, Fahira Sal (Ifma Publishing, 2023)
The purpose of this study is to determine the impact of Chief Executive Officers (CEOs) age on the bank performance in a developing Southeast Asian capital market (Indonesia). The study uses unbalanced firm-level panel data for 40 banks listed on the Indonesia Stock Exchange (IDX) from 2010 to 2018. Net interest margin and capital adequacy ratio were used to measure bank performance. The data were analyzed using panel data regression analysis, including a fixed effects model. The results show that CEOs age improve bank performance proxied by net interest margin and reduce bank performance proxied by capital adequacy ratio. Age should be considered when appointing CEOs. Older CEOs have a competitive advantage over younger CEOs, who have less experience in business.